Boho Oi Mbaru Traditions In Community Wedding Culture Mbojo Tribe in Dompu District NTB: Review The Perspective Of Islamic Law - Amrin , Amrin; Sugiyarto , Sugiyarto; Su’ud, Su’ud (Al-Insyiroh: Jurnal Studi Keislaman, 2024)
This research aims to find out how the practice and review of Islamic Law in the Boho Oi Mbaru tradition at weddings of the Mbojo Tribe community in Dompu Regency, West Nusa Tenggara Province. This research uses descriptive qualitative research with a field study approach from anthropology and sociology. The collection techniques are observation, interviews and documentation. Meanwhile, data analysis processing techniques use reduction, data presentation and drawing conclusions. The results of this research show that first, the process of implementing the Boho Oi Mbaru Tradition is the Boho Oi Mbaru Tradition, a custom of the people of Dompu Regency at weddings. This Boho Oi Mbaru tradition is carried out before the wedding ceremony. In this tradition, only the bride is bathed, while the groom is not bathed. The aim is to hope that the bride will not act like she did when she was a girl, and the community believes that carrying out this tradition can produce offspring who are worthy and obedient to their parents, and diligent in worship. Second, the view of Islamic law regarding the practice of Boho Oi Mbaru in community marriage customs is permissible because looking at the procedures for its implementation and its purpose there are no elements that give rise to sharia arguments, as long as the community customs do not conflict with the Koran and al-Hadith then permitted, unless the custom violates the provisions of Islamic law. Thus, it is necessary for the Dompu community and government to be able to maintain and maintain the identity of the Dompu in all activities, especially at weddings..